Association between metabolic health indicators and cardiorespiratory fitness in urban young and middle-aged population: a retrospective cross-sectional study - Wang, Chengshuo; Yang, Nan; Zhang, Qin; Li, Ying; Zhang, Linli; Liu, Zejian; Zhao, Ruoxuan; Qi, Jingman; Xiang, Aomeng; Fu, Yanxin; Xiong, Zheyu; Wu, Liang; et al. (Frontiers in Endocrinology, 2025)
BackgroundCardiorespiratory fitness (CRF) is an established risk factor for cardiovascular diseases (CVD). Compared with traditional clinical risk factors for CVD, CRF can better predict health status and possible adverse events. However, few studies have reported the association between multiple metabolic health indicators and CRF as an indicator of CVD risk. Therefore, this study aims to further understand the association between metabolic health indicators and CRF and to provide a theoretical basis for improving the early prevention strategies of CVD in the urban young and middle-aged population.MethodsA retrospective cross-sectional study was conducted on 889 young and middle-aged urban people who underwent health examinations in Beijing Xiaotangshan Hospital from January 2022 to December 2024. Baseline measurements of physical examination, biochemical examination, and cardiopulmonary exercise testing were obtained. The association between metabolic health indicators and CRF was analyzed. A multiple linear regression analysis was performed to assess the association between each metabolic health indicator and CRF and determine which metabolic health indicators may serve as useful predictors for assessing CRF.ResultsWe investigated the association between metabolic health indicators and CRF by adjusting for covariates (age, smoking status, and drinking status) associated with CRF. In multiple linear regression analysis, waist circumference (WC) (β = −0.196, P = 0.010), fasting plasma glucose (FPG) (β = −0.143, P < 0.001), and high-density lipoprotein cholesterol (HDL-C) (β = −0.125, P = 0.005) were significantly associated with VO2peak in young and middle-aged urban men. WC (β = −0.577, P < 0.001) and FPG (β = −0.167, P = 0.002) were significantly associated with VO2peak in young and middle-aged urban women. In addition, WC (men: β = −0.238, P = 0.003; women: β = −0.410, P < 0.001) and FPG (men: β = −0.147, P < 0.001; women: β = −0.123, P = 0.034) were significantly associated with AT in men and women.ConclusionOur results showed that WC and FPG were significantly associated with CRF in young and middle-aged urban men and women. This suggests that WC and FPG may serve as useful predictors for assessing CRF within this population.